Evaluation of Salivary Thiol/Disulfide Homeostasis and Oxidative Stress in Children with Severe Early Childhood Caries Using a Novel Method - Soğukpinar Önsüren, Asli; Mutluay, Merve; Seyithanoğlu, Muhammed; Tanriverdi, Burak (Journal of Pediatric Infectious Diseases, 2022)
Objective This study aimed to assess the role of thiol/disulfide homeostasis and oxidative stress in the saliva of children with severe early childhood caries (S-ECC).Methods Eighty children aged 3 to 6 years were involved in this case-control study. The study consisted of two groups: the study group (S-ECC) and the control group with no caries. Thiol/disulfide homeostasis and antioxidant levels were calculated after obtaining unstimulated saliva samples from all participating children.Results The native/total thiol and total oxidant status (TOS) levels of the study group were higher than those of the control group, though not statistically significant (p > 0.05). The oxidative stress index (OSI) value was significantly higher in the study group compared to the control group (p = 0.024).Conclusion Our results confirmed that the thiol/disulfide homeostasis was reduced, and disulfide formation, which is rereducible to thiol, was insufficient in children with S-ECC to compensate oxidative stress compared with the control group. Also, thiol levels were inadequate to compensate for oxidative stress, and thiol/disulfide homeostasis was not an independent parameter for S-ECC. Besides, the increases in the TOS level and OSI value show that oxidative stress had significant effects on S-ECC's etiopathogenesis.
Keywords: native thiol; thiol-disulfide homeostasis; total antioxidant status